Total site heat integration using absorption chillers for district cooling - Liew, Peng Yen (2015)
Total Site Heat Integration (TSHI) has been an established Pinch Analysis tool for inter-process heat recovery via site utility system. The Locally Integrated Energy Sector (LIES) was later introduced for the integration of intermittent energy sources and consumptions in industrial processes. The LIES concept has been utilised for the recovery of industrial low-grade heat via the district heating system. In tropical countries, space-cooling system is a major energy consumer. Residential and service buildings consume up to 59% of the total energy consumption in ASEAN countries. The energy consumption for the building sector is projected to increase by 3.1% annually between 2011 and 2035 in Malaysia. The main consumer in this sector is the cooling system that includes air conditioners and refrigerators. Waste heat-driven absorption chiller can be used for operating cooling systems. This paper proposes a TSHI methodology that incorporates the absorption chillers to reduce the industrial and space cooling demands. A case study demonstrates the use of waste heat-driven absorption chiller within the context of LIES for a district or centralised space cooling system.